Nauczanie Jana Pawła II o narodzie podczas pierwszej pielgrzymki do Polski - Sokołowski, Grzegorz (Społeczeństwo, 2022)
The thoughts of John Paul II regarding the nation and homeland are on the one hand personal experiences related to the history of Poland, which, despite difficulties, has been formed since the end of the 10th century and has shaped the experience of national unity associated with common culture, language and history. On the other hand, the teaching of the Pope in this aspect is related to the experience of the history of 20th-century Europe and in particular to the raising of national awareness of many European societies. Personalism is the foundation of the reflection on the nation. This is connected with the vision that underlies every community, including a nation, a human person.